ADDRESSING ALGORITHMIC PRICING COLLUSION IN MALAYSIAN COMPETITION LAW: CONSIDERATIONS FOR ARTIFICIAL INTELLIGENCE ETHICAL GOVERNANCE - Angayar Kanni Ramaiah,; Jaspal Kaur Sadhu Singh, (Journal of Malaysian and Comparative Law, 2025)
Artificial Intelligence (‘AI’) tools in the digital economy empower electronic agents to facilitate e-commerce transactions for digital enterprises in Malaysia. The growing number of Malaysian digital enterprises utilising digital platforms that employ AI algorithms - to customise services, predict market trends, and improve their pricing models - may result in various anti-competitive practices and tacit collusion amongst these enterprises. The absence of a formal agreement or human interaction evidencing an intent to co-ordinate poses regulatory challenges to monitor and control algorithms that trigger anti-competitive behaviour. The paper focuses on anti-competitive tacit collusion in algorithmic price setting. In the absence of formal agreement or human interaction, the possibility of colluding has caused various regulatory challenges to monitor or control such use of algorithms that may result in anti-competitive practices. This may render the Competition Act 2010 and the role of the Malaysian Competition Commission as nugatory. The paper, firstly, sets out the technological background of algorithmic pricing and collusion and its impact on consumer welfare; secondly, it examines Malaysian competition governance and the inadequacy of the regulatory tools to address the challenges presented by anti-competitive practices arising from tacit algorithmic collusion; and finally, the paper proposes the use of an AI ethical governance mechanism by the developer or deployer of the AI to ensure algorithms function ethically when used by digitised enterprises in Malaysia. This paper serves as a prescient proposal to the consequential issues of algorithmic pricing and collusion.